Recognition Of Person’s Character Trought The Shape Of Nose Using Learning Vector Quantization (LVQ) Method - Faisol, Faisol; Yuliato, Tony; Suryani, Suryani (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
Humans as social beings are never separated from interactions among others. The interaction can be done in the form of friendship, business or romance. In a relationship will be established balance and harmony if already know each other, one of them by recognizing the character. Psychology science is much discussed about character recognition one of them through the shape of the face. In this study focused on the shape of the nose and the data entered in the form of image images. The method used to identify the characters using Artificial Neural Networks is the LVQ method. From the result of the research, it can be concluded that character recognition using LVQ method has been produced from 20 trainings image there are 12 images of 4th nose type, 7 images of nose type 5, and 1 image of nose type 6th.